The Effect Of Education on Knowledge About Hypothermia and Hyperthermia at Mungkajang Public Health Center, Palopo City - Irmayanti Oka; Reti (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
Babies born through Sectio Caesarea tend to experience hypothermia due to low temperatures in the operating room, the spread of maternal heat from the center to the environment and decreased maternal central temperature. While hyperthermia is an increase in body temperature above the normal range. Hyperthermia is also usually associated with infection, either local or systemic. The purpose of this study was to determine the effect of education on knowledge about hypothermia and hyperthermia at Mungkajang Public Health Center, Palopo City. The design used in this study is a pre-experimental design with a one-group pre-test-post-test design. The sample in this study were postpartum mothers at the Mungkajang Public Health Center, Palopo City; as many as 30 people were taken during the study. In this study, the sample was taken using purposive sampling. Data analysis used paired T-test. The results showed that 13 people (43.3%) had good knowledge about hypothermia and hyperthermia before giving education, and 17 people (56.7%). Respondents who have good knowledge about hypothermia and hyperthermia after providing education are 25 people (83.3%), and 5 people have less knowledge (16.7%). There is an effect of education on knowledge about hypothermia and hyperthermia in postpartum mothers in the work area of ​​the Mungkajang Health Center, Palopo City, with a value of = 0.000 < = 0.05. This study concludes that there is an effect of education on knowledge about hypothermia and hyperthermia in postpartum mothers in the working area of ​​Mungkajang Public Health Center, Palopo City. A midwife must have a good/positive attitude which can be manifested in the form of good behavior as well. Therefore, it is worth continuing to improve and develop your midwifery knowledge.